Disease burden and clinical severity of the first pandemic wave of COVID-19 in Wuhan, China - Juan Yang (Nature Portfolio, 2020)
Here the authors analyze disease burden and clinical severity of COVID-19 during the first wave in Wuhan, China in comparison to past influenza virus pandemics and COVID-19 in the US and Canada. These estimates of symptomatic cases, medical consultations, hospitalizations and deaths should guide preparedness for this disease.